The implementation of House of Risk and Interpretive Structural Modeling Approach To Risk Mitigation of Supply Chain Problems In The Fertilizer Industry - Muhamad Mukhtarul Haqi; Farida Pulansari; Sinta Dewi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
PT. Petrokimia is seeing escalating difficulties in their supply chain system. Supply Chain Risk Management evaluations can be conducted using many methodologies. Supply Chain Risk Management (SCRM) is a process that involves identifying, evaluating, and reducing risks that have the potential to disrupt the smooth operation of the supply chain, which includes the movement of goods and services. This research combines prior studies by employing a hybrid approach known as House of Risk (HoR) and Interpretive Structural Modeling (ISM). The House of Risk (HoR) method is employed to identify registered risk agents by assessing the importance of preventative measures and selecting priority actions. The ISM methodology is utilized in this study to construct a structural framework for examining the contextual associations among risk elements in the company's supply chain. The organization experienced many hazards, with a total of 20 risk events generated by 30 risk agents across the Plan, Source, Make, Delivery, and Return stages. According to the Pareto diagram concept, there are 11 risk agents that require prioritized mitigation. Out of the 10 risks identified, 1 risk is categorized as dependent while the remaining risks fall within the autonomous sector. Among the 11 primary risk factors, the one with the highest ARP value is anticipated to serve as a benchmark for addressing several hazards that have arisen in the company's supply chain. The research has studied and generated mitigation measures to avoid production losses, time losses, and quality reduction resulting from hazards that may hinder the achievement of company objectives.